Forensic Linguistics: Netizens’ Hate Speech Implicature on the Issue of the 2024 Presidential Election (TikTok Social Media Case Study) - Nurul Fadhilah; Budyi Suswanto; Yuni Putri Utami (Technium Social Sciences Journal, 2023)
In the area of language, vocabulary could be an indicator in materials for legal investigations. One of them is the vocabulary contained in hate speech. The aim of this research is to analyze netizens’ hate speech implicature on the issue of the 2024 presidential election by using forensic linguistics approach. This study is qualitative descriptive with data in the form of a collection of netizens’ hate speech written in the comment boxes of ten Tiktok videos. The result shows if implicatures of hate speech that arise on social media regarding the political issue of the 2024 presidential election mostly revolve around the performance and sensitive issues of ethnicity, religion, race, and intergroup (SARA) attached to the potential presidential candidates. These hate speeches categorized as, (1) insults, (2) defamation, (3) provoking, (4) inciting, and (5) spreading fake news. Awareness is needed that there are limitations, such as respect for human rights (HAM), within the freedom of expression. In addition, awareness of the criminal aspects contained in the Criminal Code (KUHP) and the ITE Law is also crucial, so that netizens exercise greater caution in expressing their thoughts, especially in social media, as it leaves a digital footprint.